2017
DOI: 10.5114/amscd.2017.66862
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of IL28B gene and response to pegylated interferon α2a in chronic hepatitis B

Abstract: A b s t r a c tIntroduction: Because of its worldwide prevalence, chronic hepatitis B constitutes a significant global health issue. Chronic hepatitis B virus (HBV) infection affects about 350 million people, with 1 million deaths annually due to its sequelae. The unique way of replication makes HBV difficult to eradicate with the available treatment. Interferon is currently the only option offering a "curative treatment strategy". Predictors of a sustained response to interferon are desired. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It is used to treat solid tumors, lymphomas and sarcomas with a high degree of malignancy [2]. Single nucleotide polymorphisms (SNPs) in genes that encode antineoplastic drug-metabolizing enzymes could have effects on drug efficacy, toxicity and life span [3][4][5]. The CYP2B6 gene has more than 29 SNPs, but only CYP2B6*2 and CYP2B6*6 are functionally significant and result in decreased enzyme activity [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is used to treat solid tumors, lymphomas and sarcomas with a high degree of malignancy [2]. Single nucleotide polymorphisms (SNPs) in genes that encode antineoplastic drug-metabolizing enzymes could have effects on drug efficacy, toxicity and life span [3][4][5]. The CYP2B6 gene has more than 29 SNPs, but only CYP2B6*2 and CYP2B6*6 are functionally significant and result in decreased enzyme activity [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…(T/G), and HLA-DP (rs3077) were analyzed in Chinese-origin patients with HBV infection who tested negative for HBsAg [19].The authors reported significantly more frequent HBsAg loss among HLA-DP1 (rs3077) AA genotype carriers than in rs179860CC and rs8099917GG allele carriers. The above-mentioned allele configurations activate the immunological response of the host, leading to non-cytolytic degradation of cccDNA in the hepatocyte nuclei [19].…”
Section: P R E P R I N Tmentioning
confidence: 99%
“…Recently, tumor necrosis factor α (TNF-α) has been associated with heavy alcohol intake [12]. An increased production of cytokines by blood monocytes and Kupffer cells in alcoholic steatosis patients and in animal models with alcohol-induced liver damage has been shown [13][14][15]. Additionally, excessive TNF-α production depends on the amount of alcohol ingested [16].…”
Section: Introductionmentioning
confidence: 99%